Efektifitas Model Problem Based Learning pada Materi Larutan Elektrolit dan Non Elektrolit Berbantuan Media PowerPoint Interaktif di SMA Negeri 2 Muaro Jambi - Falah, Mutiara Al; Malik, Affan; Epinur, Epinur (Lembaga Yasin AlSys, 2024)
This study aims to determine the application of the problem based learning model assisted by interactive PowerPoint media to be significantly effective on electrolyte and non-electrolyte solution materials at SMA Negeri 2 Muaro Jambi. This research is a form of Quasi Experiment research with the type of Posttest only control design. This study describes a causal relationship involving two randomly selected sample classes. The research instruments are interview sheets, essay tests, and observation sheets. The data analysis technique used was qualitative data analysis (observation sheets of teacher activities) and quantitative data analysis (results of the posttest and observation sheets of student activities). The results of this study showed that student learning outcomes in the experimental class were greater than those in the control class, namely 73.86% and 63.97%. Based on the statistical test, the results showed a significance value of 2-way (t-tailed) 0.000 <0.05, indicating a significant difference between the two data. for the posttest value of the experimental class has an average of . then we get an effect size of 1.12 with a high interpretation. This shows that the class with the PBL model assisted by interactive PowerPoint media is more effective than the class with the PBL model without interactive PowerPoint. Based on the results of the research that has been done, the conclusion is that applying the problem-based learning model assisted by interactive PowerPoint media is significantly more effective in the material for electrolyte and non-electrolyte solutions in class X MIPA 1 SMAN 2 Muaro Jambi.